The birds that Audubon missed : discovery and desire in the American wilderness - Kaufman, Kenn (Avid Reader Press, 2024)
"Naturalist Kenn Kaufman examines the scientific discoveries of John James Audubon and his artistic and ornithologist peers to show how what they saw (and what they missed) reflects how we perceive and understand the natural world"--